1998
DOI: 10.22358/jafs/69958/1998
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of passive immunity in domestic ungulates

Abstract: The ungulates possess an epteriochondrial placenta, which separates the maternal and foetal blood systems and thus reduces the permeability of the placenta to small molecules. Thus, in these species, the colostral imminoglobulins are the main source of protection factors which aid survival in the first days of life. This review deals with several aspects of passive immunity in ungulate neonates: the type and the origin of colostral immunoglobulins and factors which influence their production in the mother and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In addition to immunoglobulins, the colostrum contains a variety of factors that may accelerate the process of closing of the intestinal barrier (Tyler and Ramsey, 1993). It seems that the closing of the intestinal barrier depends on the uptake by the organism of the newborn of an appropriate quantity of biologically active factors and immunoglobulins present in the colostrum within a specified time window (Grognet and Duvaux-Ponter, 1998). It was shown that the closing of the intestinal barrier was extended in piglets that did not receive the appropriate amount of biologically active factors from the colostrum.…”
Section: How Do the Changes In The Enterocyte Structure Fit Into An Omentioning
confidence: 99%
“…In addition to immunoglobulins, the colostrum contains a variety of factors that may accelerate the process of closing of the intestinal barrier (Tyler and Ramsey, 1993). It seems that the closing of the intestinal barrier depends on the uptake by the organism of the newborn of an appropriate quantity of biologically active factors and immunoglobulins present in the colostrum within a specified time window (Grognet and Duvaux-Ponter, 1998). It was shown that the closing of the intestinal barrier was extended in piglets that did not receive the appropriate amount of biologically active factors from the colostrum.…”
Section: How Do the Changes In The Enterocyte Structure Fit Into An Omentioning
confidence: 99%
“…Bioactive milk components, being the product of milk protein digestion, were recently the subject of several extensive reviews by Wong et al (1996), Meisel (1997), Rudloff and Kunz (1997), Schanbacher et al (1997), Tirelli et al (1997), and therefore will be only briefly mentioned in the section concerning processing of milk. Milk immunoglobulins are reviewed in this issue by Grongnet and Duvaux-Ponter (1998).…”
Section: Bioactive Proteins and Peptides In Colostrum And Milkmentioning
confidence: 99%
“…As a consequence, receptivity to dietary management is likely to occur at different stages of development. Exemplary of this is the limited and species-specific period for acquisition of passive immunity by neonates (reviewed by Grongnet and Duvaux-Ponter, 1998). There is a need to identify "windows of opportunity" during which the GIT is responsive to dietary management.…”
Section: Perspectivesmentioning
confidence: 99%